2015
DOI: 10.1080/15476286.2015.1017213
|View full text |Cite
|
Sign up to set email alerts
|

RBM4-MEF2C network constitutes a feed-forward circuit that facilitates the differentiation of brown adipocytes

Abstract: Keywords: alternative splicing, brown adipocytes, MEF2C, miR-1, RBM4Myocyte enhancer factor 2c (MEF2C) is the MADS-box type transcription factor involved in the differentiation of cardiac and skeletal muscle and synaptic formation. Alternatively spliced transcripts of the MEF2C gene were proven to encode isoforms which exert distinct functions in transcriptional regulation. During the differentiation of brown adipocytes, upregulated RBM4 enhanced skipping of the MEF2Cg region which functions as a transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…However, in this study, ssc-miR-1 and ssc-miR-133a, with highly abundant expression, were up-regulated in the adipose tissue of the Laiwu pig. Moreover, previous studies suggest that ssc-miR-1 and ssc-miR-133a are related to adipocyte differentiation in humans and rats [41,42]. Therefore, ssc-miR-1 and ssc-miR-133a may increase lipometabolism in pigs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in this study, ssc-miR-1 and ssc-miR-133a, with highly abundant expression, were up-regulated in the adipose tissue of the Laiwu pig. Moreover, previous studies suggest that ssc-miR-1 and ssc-miR-133a are related to adipocyte differentiation in humans and rats [41,42]. Therefore, ssc-miR-1 and ssc-miR-133a may increase lipometabolism in pigs.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that some differentially and abundantly expressed miRNAs (down-regulated miRNAs: ssc-let-7i, ssc-miR-21, ssc-miR-27b-3p and up-regulated miRNAs: ssc-miR-1, ssc-miR-133a-3p, ssc-miR-486) were responsible for regulating adipogenic differentiation [36][37][38][41][42][43]. ssc-miR-1 and ssc-miR133a were found extensively in skeletal muscle tissues while ssc-miR-21, ssc-miR-27b-3p, and the Let-7 family play important roles in adipomuscle and myocardial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The SPTB interacts with phospholipids in natural [63] and model membrane systems [64] and has a role in controlling the fluidity of the inner lipid leaflet of the cell membrane (reviewed in [65]). MEF2C is a transcription factor involved in skeletal muscle differentiation; however, it has been reported as a constituent of a mechanism that programs gene expression involved in development of brown adipocytes [68]. MEF2A and MEF2D isoforms exhibited in vivo differential expression in mammalian striated muscle and white adipose tissue of insulindeficient diabetic mice [69].…”
Section: Epigenome-wide Association Analysis Showed Dna Methylation Cmentioning
confidence: 99%
“…While cnidarians have no identified period orthologue, and CK1 acts at the protein level, homologues of both clock and pdp1 ( bzip1 and bzip3 ) are also present in the DEGs in this group along with lark . Lark / rbm4 has also been reported to regulate splicing of mef2 in mammals (Lin, ). No major phase shifts in clock gene transcription cycles were observed, although they were common in other groups of genes identified in the GSEA, including “cellular response to stress” (Figure ).…”
Section: Resultsmentioning
confidence: 99%